Komparative Theologie - ein Ausweg aus dem Grunddilemma jeder Theologie der Religionen? - Stosch, Klaus von (Zeitschrift für katholische Theologie, 2002)
Many religious believers want to appreciate people of different religious faith without giving up the claim to truth of their own religious tradition. But the solutions of this dilemma proposed by the theology of religions (inclusivism and pluralism) are not able to fulfill both desires. The author tries to show that traditional theology of religions is for philosophical reasons not able to combine both interests in a sufficient way even though the Christian believers have to stick to the possiblity of a solution of this dilemma. The author proposes a solution which is a form of comparative theology following some basic insights of the later Wittgenstein, especially Wittgenstein's insight in the regulative dimension of religious belief. In contrast to traditional theology of religions, such a comparative theology turns the attention to the individual case in the interreligious dialogue and concentrates on the regulative and world-picture-constitutive role of religious belief.